Interdisciplinary Learning of Islamic Religious Education in Vocational High School - Alwi, Itsnaini Muslimati; Tobroni; Faridi (AT-TAJDID: Journal of Islamic Education, 2025)
In this globalization era, the challenge for Islamic religious education in vocational schools is not only the delivery of religious material, but also how to integrate religious values into students' daily lives. The purpose of this paper is to discuss 1) Interdisciplinary of Islamic Religious Education in Schools, 2) The Implementation of Interdisciplinary Islamic Education in Schools. The method used is a qualitative approach. Data collection was done through observation and interviews. The results of this study include: 1) The Interdisciplinary approach is a research approach in which there is a transfer of a discipline into other disciplines in solving certain problems so that it can give birth to a new discipline or new methods, 2) The interdisciplinary approach in Islamic religious education learning is believed to make it "alive" and meaningful for students.